Etiology of Maternal Mortality at Nepalgunj Medical College - B.C., Durga; Neupane, Ganesh Prasad; Rai, Maya; Sharma, Aseem (Journal of Nepalgunj Medical College, 2018)
Introduction: Maternal mortality is an indicator of the quality of obstetric care in a community directly reflecting the utilization of health care services available. Maternal mortality has been recognised as a public health problem in the developing countries. Aim and Objective: To analyse the etiology of maternal deaths. Material and Methods: This descriptive study was conducted in the gynaecology and obstetrics department of the Nepalgunj Medical College Teaching Hospital Banke Nepal for a period of two years from august 2016-august 2018. All cases of maternal deaths in line with the definition of World Health Organization have been included. Data were collected and analyzed. Results: Twenty three (23) maternal deaths were identified during the study period. 69.56% of deaths occurred due to direct obstetric causes. Uncontrollable postpartum haemorrhage with 37.5 % was the leading cause of maternal death followed by eclampsia (18.75%) and sepsis (18.75%). Indirect causes were dominated by heart disease. Maximum 56.5% of deaths had occurred after 48 hours of admission. Conclusions: Haemorrhage, eclampsia and infections are the main causes of maternal deaths in our study. access to emergency medication, transfusion and anaesthetic and surgical teams in hospitals but also through the involvement of religious leaders, traditional and any community to better understand the population obstacles to reducing maternal mortality.